Solid-State Anaerobic Digestion of Organic Solid Poultry Waste for Biomethane Production - Faryal Fatima; Raghava R. Kommalapati (Bioengineering, 2025)
This study examines biodegradability (BD) and optimum conditions for the solid-state anaerobic digestion (SS-AD) of organic solid poultry waste (organs, intestines, offal, and unprocessed meat) to maximize biomethane production. Three main parameters, substrate-to-inoculum (S/I) ratio, pH, and temperature, were evaluated for the SS-AD of organic solid poultry waste. pH was evaluated at non-adjusted pH, initially adjusted pH, and controlled pH conditions at a constant S/I ratio of 0.5 and temperature of 35 ± 1 °C. The S/I ratios were examined at (0.3, 0.5, 1, and 2) at a controlled pH of ≈7.9 and temperature of 35 ± 1 °C. The temperature was assessed at mesophilic (35 ± 1 °C) and thermophilic (55 ± 1 °C) conditions with a constant S/I ratio of 0.5 and controlled pH of ≈7.9. The results demonstrate that the highest biomethane production and BD were achieved with a controlled pH of ≈7.9 (689 ± 10 mg/L, 97.5 ± 1.4%). The initially adjusted pH (688 ± 14 mg/L, 97.3 ± 1.9%) and an S/I ratio of 0.3 (685 ± 8 mg/L, 96.8 ± 1.2%) had approximately equivalent outcomes. The thermophilic conditions yielded 78% lower biomethane yield than mesophilic conditions. The challenge of lower biomethane yield under thermophilic conditions will be resolved in future studies by determining the rate-limiting step. These observations highlight that SS-AD is a promising technology for biomethane production from solid organic poultry waste.